O trabalho em saúde junto ao SUS a partir da experiência na extensão popular: desafios e potencialidades - Leite, Maria Francilene (2014)
This research has its beginning with the experience in the Projeto Educação Popular e Atenção à Saúde da Família (PEPASF). This is an extension project of Federal University of Paraíba guided by the theoretical and methodological assumptions of Popular Education. Throughout 16 years of existence, this project has contributed to the capacitation of health professionals with the perspective of care integrality, critical consciousness and political maturation. However, the way how SUS is organized in many states and cities difficult the exercise of important elements for health work: workers autonomy and protagonism; teamwork; community approach; favoring of popular participation and; humanized work on health. In this way, the aim of this research was to analyze the health work along with SUS from the experience on popular extension. We conducted a descriptive, exploratory and cross-sectional study, with quantitative and qualitative approaches. The study subjects were health professionals that spent a year at the Popular Extension, who have complete the graduation during the period of 2004 to 2012 and that act or acted directly in SUS. The collect of empirical data was conducted through a structured questionnaire and a semi structured interview. In quantitative analysis, we performed the non-parametric tests of Wilcoxon and Mann-Whitney, and the cluster analysis. For the qualitative data, we used the thematic analysis. The results indicate that the professionals egressed of the Popular Extension have difficulty to implement, in work, the learnings provided by the experiences in this extension. However, the cluster analysis identified a subjects group who has more facility to implement these learnings in work with the SUS. We noticed that the Popular Extension represents a significative mark in health professionals formation and that they have a great potential to work with the SUS. The professionals egressed of the Popular Extension also face major challenges in the world of work SUS, such as: live with the disappointment and discouragement arising from the hardness of the work process in health; deal with centralization in the management of public health services; live with clientelism and partisan political involvement of some health professionals; respond to the high demand for health care and fulfill an extensive workload. The practices in Popular Extension and work in health with the SUS, despite showing similarities, are conducted by different perspectives and interests. Therefore, it is important that, even in health education, students have access to SUS in a critical perspective and not purely idealized. We hope that the community approximation comes to be understood as a concrete pedagogical element of health education and not as an alternative practice of extension responsibility and other extracurricular proposals.